Higher Education and the Politics of Disruption - Giroux, Henry A. (Chowanna, 2020)
At its best education is dangerous because it offers young people and other actors the promise of racial and economic justice, a future in which democracy becomes inclusive and a dream in which all lives matter. In a healthy society universities should be subversive; they should go against the grain, and give voice to the voiceless, the unmentionable and the whispers of truth that haunt the apostles of unchecked power and wealth. Pedagogy should be disruptive and unsettling and push hard against the common sense vocabularies of neoliberalism and its regime of affective management.